World cattle: V. 1. cattle of Europe, South America, Australia and New Zealand; V. 2. cattle of Africa and Asia; V. 3. cattle of North America - Haas, H.J. de; Murage, J.; Smith, G.P. (Food and Agriculture Organization of the United Nations, 1975)
Generally two types of indigenous sheep can be differentiated the blackhead Persian or Somali sheep, a fat ramped sheep if the northern and North-eastern parts of Kenya, and the Red Masai, a fat-tailed sheep, more frequently to be seen in central and southern Kenya. Up grading of red Masai or black Persian sheep to Dorper in the drier parts of Kenya, are essential with the aim of increased meat out put. There are strong indications that under good management levels indigenous ewes are producing excellent crossbred lambs from Dorper sires.